Coronary Artery Tortuosity: Beyond an Incidental Angiographic Finding:Implications for Myocardial Mechanics Evaluated by Speckle-Tracking Echocardiography - Ahmed Shaker, Mohamed Wafaie M. M. Aboleineen , Muhammad El Sayed El Sayed Moustafa, Shimaa Gamal Zein ELabdeen (Cuestiones de Fisioterapia, 2024)
Background: Coronary artery tortuosity (CAT) has traditionally been regarded as a benign angiographic finding with limited clinical significance. However, accumulating evidence suggests that CAT may be associated with altered coronary hemodynamics, reduced distal perfusion pressure, impaired coronary flow reserve, and myocardial ischemia even in the absence of obstructive coronary artery disease. Patients with CAT frequently present with angina-like symptoms, positive stress tests, or reversible perfusion abnormalities despite normal epicardial coronary arteries. In recent years, advances in myocardial deformation imaging have enabled the detection of subtle abnormalities